The role of industry 4.0 in supply chain sustainability: Evidence from the rubber industry - Krisada Chienwattanasook; Nartraphee Tancho; Suraporn Onputtha; Chanathat Boonrattanakittibhumi; Thanaporn Sriyakul; Phutthiwat Waiyawuththanapoom (My University, 2022)
The objective of the current study is to examine the role of Industry 4.0 in supply chain sustainability (SCS). To examine the effect of Industry 4.0 on SCS, the big data technology is considered. As the supply chain process requires a significant data handling system among the companies, however, companies are lacking in this area. Therefore, the relationship between data storage, data transformation, data utilization, order management and SCS were examined. Data was collected from the rubber industry. For the purpose of data collection, questionnaires were used, and data were collected from the rubber companies of Indonesia. Results of this study shows that Industry 4.0 has a vital role in SCS. Implementation of Industry 4.0 among the rubber companies shows a positive effect on SCS. Particularly, the applications of big data technology have a vital role in order management and SCS. Big data technology has a significant positive effect on SCS. Big data technology has a positive role to promote order management which further influences positively on SCS.
Keywords: Digital Transformation in Industry